The Mediating Role of Social Media Usage as a Learning Tool on Students’ Academic Performance: A Structural Equation Modelling (SEM-AMOS) Approach - Mat Zin, Siti Hasma Hajar; Zakaria, Siti Haslini; Hassim, Nor Hidayah; Che Md Nor, Rumaizah; Rosnan, Suhanah; Mohd Shafee, CT Munirah Niesha (Information Management and Business Review, 2024)
Social media is used in many aspects of modern life. Lately, higher education has also expanded its focus to include globalized online learning using social media. Educational establishments have acknowledged that social media gives students a chance to interact with teachers, other students, and higher authorities. However, there is little information available on it in educational settings, especially in the classroom. Only a small number of studies in Malaysia have specifically examined social media, even though many studies have looked at how social media influences the academic performance of university students. Therefore, we conducted this quantitative study to determine whether social media usage mediates the relationship between educational variables and academic performance among students enrolled in Malaysian public higher education institutions. We conducted a cross-sectional study at UiTM Segamat, involving 388 respondents. The findings demonstrate that social media usage mediates the relationship between students’ performance and perceived usefulness, perceived enhanced communication, and resource sharing. Social media use does not mediate perceived ease of use, collaborative learning, or perceived enjoyment of students’ performance. To use social media as a teaching tool, particularly in higher education institutions, the research findings bring new knowledge to the field. The higher education community may share knowledge anytime and anywhere. This platform allows educators and students to interact with one another after learning sessions, which will help the student succeed academically.